Deskripsi Kemampuan Pemecahan Masalah Pada Soal Cerita Materi Pythagoras Ditinjau Dari Tipe Kepribadian Myers Briggs Type Indicator (MBTI) - Choiruzzain, Desca (Jurnal AlphaEuclidEdu, 2024)
Problem-solving skills should be possessed by every learner. In order for problem-solving to provide meaningful and profound knowledge and experiences to learners, determining problem-solving strategies can be grouped according to the nature of the problem to be solved. There are several factors influencing problem-solving skills, one of which is motivation influenced by personality. One personality type is the Myers Briggs Type Indicator (MBTI). This research aims to determine the problem-solving abilities of students in Pythagorean theorem story problems based on the Myers Briggs Type Indicator (MBTI) personality types in the eighth-grade class E of State Junior High School 23 Pontianak. The research method used is descriptive with a qualitative research design. The data sources for this research are eighth-grade students in class E, and the data include problem-solving ability test sheets, MBTI personality type questionnaires, and interview results with students. The research results show that there are 12 MBTI personality types in class E of State Junior High School 23 Pontianak, including INFP, ISFJ, ESTP, ESTJ, ISFP, INTJ, ENFP, ESFP, ISTJ, INFJ, ENTJ, ISTP. These 12 personality types can execute the problem-solving steps according to Polya's theory.Keywords:  Problem Solving, Pythagorean Theorem, Polya, MBTI